If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = x Solving 0 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 0 + -1x = x + -1x Remove the zero: -1x = x + -1x Combine like terms: x + -1x = 0 -1x = 0 Divide each side by '-1'. x = 0 Simplifying x = 0
| 24-8x+3x= | | (3X^2+X+1)-(2X^2-3X-5)=0 | | 2u^2+3u-5=0 | | (5x+x)+(9y+18)=90 | | 5t-12=5t-13 | | -2=-7x+6x | | 2k^2+7k-35= | | 6-3(3x-4)=4 | | 4x+32=4(2x+4) | | 10x-6=8x+134 | | 5+2x=2.5x | | (x+2)7.50=30 | | 3x=7x-32 | | 3w^2+10w+7=0 | | 93-107=-8(-4y)-17(2y)+y | | -(5xy-12)+2(3xy+4)= | | 6[4-(-2x-4)]=36x+96 | | 5s=150 | | 29+x^2=0 | | 30+2k+5.5=10 | | 14-3(4n-1)-9= | | 2(5)=3 | | 16x^2+9=y | | -4+5=71 | | -140=-10(-2b) | | W+12=8+5W | | 3.5+3.5+5+0+x=5 | | 3x+8+2x=48 | | 0=7x^2-3x-36 | | 3r^2+8r+32= | | 5x-3y+9=0 | | -4.9x^2+42x-25=0 |